1977
DOI: 10.1002/esp.3290020208
|View full text |Cite
|
Sign up to set email alerts
|

Measurements of rainsplash erosion and the formation of colluvium beneath deciduous woodland in the Luxembourg Ardennes

Abstract: SUMMARYIn wooded dry valleys in the Luxembourg Ardennes a gravelly and slightly organic colluvial deposit occurs. The depositionary nature of the material is ascertained by its micromorphological characteristics and its position on top of a truncated argillic horizon of an older soil. Pollen analysis revealed the colluvium to have been formed in the last 500 years, the lower 37 cm in the Haarts valley under non-forest (presumably arable land) conditions and the upper lOcm under today's oak woodland. A formatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0
4

Year Published

1977
1977
2011
2011

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(25 citation statements)
references
References 9 publications
1
20
0
4
Order By: Relevance
“…They concluded that most of the colluvium studied under arable land had a late medieval or younger age, again because of the presence of Fagopyrum pollen. In another paper Kwaad (1977) states that colluviation rates were on average 0.8 mm yr À1 between 1400 and 1800 and have declined to 0.6 mm yr À1 since then. Riezebos and Teunisse (1992) observed that the water-sediment regime in streams must have changed in the early Sub-Atlantic period (3000-2000 BP).…”
Section: Historical Evidence Of Erosionmentioning
confidence: 96%
See 1 more Smart Citation
“…They concluded that most of the colluvium studied under arable land had a late medieval or younger age, again because of the presence of Fagopyrum pollen. In another paper Kwaad (1977) states that colluviation rates were on average 0.8 mm yr À1 between 1400 and 1800 and have declined to 0.6 mm yr À1 since then. Riezebos and Teunisse (1992) observed that the water-sediment regime in streams must have changed in the early Sub-Atlantic period (3000-2000 BP).…”
Section: Historical Evidence Of Erosionmentioning
confidence: 96%
“…The soils in the Oesling are mainly developed in slates and phyllites, which show relatively good infiltration rates, and hence current erosion rates on the planation surfaces seem to be relatively unimportant (Imeson and Jungerius, 1974;Kwaad, 1977;Kwaad and Mücher, 1977), as indicated by studies carried out in the region around Wiltz. The only relevant surface erosion process under forest at present is splash erosion, in places where the soils becomes bare, frost action and creep (Imeson, 1976(Imeson, , 1977Imeson and Kwaad, 1976;Kwaad, 1977). The presence of bare soils and hence increased erodibility are almost completely related to faunal activity such as the burrowing activity of earthworms and moles.…”
Section: The Oeslingmentioning
confidence: 96%
“…Il déplace des brindilles et des éléments de la taille des limons et des sables (fraction inférieure à 2 cm) par saltation (Avenard, 1963 ;Lenoble, 2003), mais aussi des cailloux (1-5 cm) par reptation sur une faible distance (Kirby & Kirby, 1974 ;Kwaad, 1977 ;Poesen, 1987 ;Sala, 1988 ;. Le ruissellement diffus se traduit par des pavages résiduels et des traces de ruisselets.…”
Section: -Les Différentes Formes Du Ruissel-lement Identifiées Sur Leunclassified
“…C'est un matériel homogène, non stratifié, à texture de limon sablo-argileux. Il est difficile de déterminer si l'accrétion du sol résulte d'une sédimentation relativement continue (colluvionnement lent lié l'impact des gouttes de pluie, au ruissellement diffus et à l'activité de la faune) (Kirkby, 1967 ;Kwaad, 1977 ;Hazelhoff et al, 1981) ou si elle ne reflète qu'un nombre limité d'événements, les dépôts ayant ensuite été totalement homogénéïsés par l'activité biologique. L'absence de graviers dans les dépôts, alors que des matériaux grossiers étaient disponibles à l'amont, plaide en faveur de la première hypothèse, c'est-à-dire d'une sédi-mentation lente et sélective de particules fines.…”
Section: Sédimentationunclassified
“…Cependant, en considérant une épais-seur moyenne de l'horizon argilique égale à 50 cm et une durée de formation couvrant la période Atlantique et le début du Subboréal, soit approximativement 4000 ans, on obtient un taux moyen d'accrétion verticale d'environ 12,5 cm par millier d'années. Ce taux est faible et peut se comprendre comme le simple résultat d'un colluvionnement sous forêt (Kwaad, 1977 ;Sala, 1988). Il reste notamment très modeste en comparaison de celui calculé pour les colluvions gallo-romaines surmontant le paléosol, qui est d'environ 250 cm par millier d'années.…”
Section: Sédimentationunclassified